Building resilience and performance in turbulent times: The influence of shared leadership and passion at work across levels - Andrés Salas-Vallina; Yasin Rofcanin; Mireia Las Heras (BRQ Business Research Quarterly, 2022)
The COVID-19 pandemic has tested health care professionals to the extreme. This study investigated the re-enchanting effect of shared leadership and passion at work in the context of public health care. This study advances on the Self-Determination Theory to suggest that shared leadership has a positive effect on resilience and performance through passion at work at different levels of analysis. A sample of 518 physicians working in Spanish public hospitals was used. The results showed that shared leadership was associated with team and individual outcomes via passion at work at team level, while no significant mediating effect was found for passion at work at the individual level. The theoretical and practical implications of the findings are discussed, limitations are considered, and future research directions are suggested.
Keywords: M12; M54; 650; passion at work; performance; resilience; Shared leadership